Influence of structural irregularities on seismic performance of RC frame buildings - Ghimire, Krishna; Chaulagain, Hemchandra (Journal of Engineering Issues and Solutions, 2021)
Irregular building structure is frequently constructed across the globe for fulfilling aesthetic as well as functional requirements. The structures with irregularities are the common building type in earthquake-prone country like Nepal. However, a post-earthquake reconnaissance survey reports revealed the high seismic vulnerability of the building with structural irregularities. In this context, the present study explores the influence of structural irregularities on performance of reinforced concrete (RC) frame structure. To this end, the structural irregularities are created in in the building structures. The geometrical irregularities are created by removing the bays in different floor levels. Likewise, the effect due to mass irregularities are studied by considering the swimming pool and game house at different floor levels. Furthermore, the stiffness irregularities are formulated by removing the building columns at different sections. All these irregularities are studied analytically in finite element program with 3-D structural models. The numerical analysis is done with non-linear static pushover and time history analysis. The results are analyzed in terms of fundamental time period, storey shear, storey displacement, drift and overturning moment. The results indicate that the level of irregularities significantly influenced the behavior of structures.